Spirituality, Religion, and Health: The Role of Communication, Appraisals, and Coping for Individuals Living with Chronic Illness - Rafferty, Katherine A. (Journal of religion and health, 2015)
Currently, 10 % of Americans are living with a chronic illness. One coping mechanism for individuals living with chronic illness is religion and/or spiritual (R/S). To better explicate the relationship among R/S and psychological well-being, we conceptualize R/S as an interpersonal process involving conversations that may facilitate positive reappraisals. We use a mixed-method approach from data collected from 106 participants, involving a content analysis of R/S conversations and test Burleson and Goldsmith’s (Handbook of communication and emotion: research, theory, applications, and contexts, Academic Press, San Diego, pp 245-280, 1998) appraisal-based comforting model. Partial support for the model was found. In addition, the majority of R/S conversations were considered positive, helpful, and supportive. Theoretical and practical implications are discussed.